2023
DOI: 10.1111/imr.13213
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity of human skin‐resident memory T cells in health and disease

Abstract: Summary The human skin is populated by a diverse pool of memory T cells, which can act rapidly in response to pathogens and cancer antigens. Tissue‐resident memory T cells (TRM) have been implicated in range of allergic, autoimmune and inflammatory skin diseases. Clonal expansion of cells with TRM properties is also known to contribute to cutaneous T‐cell lymphoma. Here, we review the heterogeneous phenotypes, transcriptional programs, and effector functions of skin TRM. We summarize recent studies on TRM form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 241 publications
0
1
0
Order By: Relevance
“…Further implicating TRMs in disease pathogenesis, studies have observed that the TCR sequence from fixed drug eruption patient T-cells derive from local cytotoxic TRMs rather than the central memory pool ( Strobl and Haniffa, 2023 ). Additionally, TCR repertoire analysis in TEN patients revealed massive clonal expansion of CD8 + lymphocytes which derive from a TEM phenotype, providing further supporting evidence of their involvement ( Villani et al, 2021 ).…”
Section: Why the Skin?mentioning
confidence: 99%
“…Further implicating TRMs in disease pathogenesis, studies have observed that the TCR sequence from fixed drug eruption patient T-cells derive from local cytotoxic TRMs rather than the central memory pool ( Strobl and Haniffa, 2023 ). Additionally, TCR repertoire analysis in TEN patients revealed massive clonal expansion of CD8 + lymphocytes which derive from a TEM phenotype, providing further supporting evidence of their involvement ( Villani et al, 2021 ).…”
Section: Why the Skin?mentioning
confidence: 99%
“…Recent studies highlighted the involvement of resident memory T cells (T RM ) in disease pathogenesis [ 24 , 27 , 29 31 ]. T RM are long-lived memory T cells that persist in tissues like the skin and are characterized by a specific transcriptional program [ 32 , 33 ]. They express characteristic cell surface markers involved in their retention in the tissue, such as CD69, CD103, or CD49a, the latter marker defining a subset of T RM cells with cytotoxic properties [ 29 , 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is now clear that the micro environment plays a crucial role in the formation and regulation of T RM . Indeed, the expression of CD103 is dependent on transforming growth factor (TGF)-β [ 36 ], and a growing number of studies reported the involvement of several pro-inflammatory cytokines involved in T RM homeostasis, such as IL-15, IL-12, IL-18, IL-33, IFNγ, TNFα [ 32 ]. The presence of T RM in vitiligo skin is undoubtedly linked to the recurrence of lesions on previously affected anatomical sites that have repigmented following treatment [ 37 ], as shown in psoriasis or atopic dermatitis [ 38 40 ].…”
Section: Introductionmentioning
confidence: 99%